Financial Performance Analysis Of Zakat Collection Institutions: A Case Study Of Baznas Dki Jakarta For The 2021–2024 Periode - Bagas Irfan; Aniqotuz; Dimassamsa; Muhammad Shodiqin (Jurnal I-Philanthropy, 2026)
Good and transparent zakat management is crucial for building public trust, especially in DKI Jakarta, which has significant zakat collection potential. Good financial performance reflects professional governance and ensures that funds are properly distributed to those entitled to receive zakat. This study evaluates the financial performance of BAZNAS DKI Jakarta from 2021 to 2024, using indicators of effectiveness, efficiency, fund growth, and distribution activities. Data were taken from annual financial reports, and analysis was conducted using the non-profit organization's financial ratios. The results show that fund collection has consistently increased, with a good distribution ratio. The level of operational efficiency is also good, despite variations in management costs. This indicates that BAZNAS DKI Jakarta's financial performance is healthy and accountable. The study's conclusions emphasize the importance of strengthening the financial system, information transparency, and the use of digital technology to improve performance. It is recommended that further research expand the scope of study by comparing BAZNAS in other provinces or with non-governmental zakat institutions..